Bariatric surgeons' experiences of working in the first year of the pandemic - Yitka N. H. Graham; Kamal Mahawar; Rishi Singhal; Brij Madhok; Wah Yang; Manel Riera; Pedro Martinez‐Duartez; Sjaak Pouwels; Mitesh Sharma; Catherine Hayes (Wiley, 2023)
Abstract Background The first year of the Covid‐19 pandemic saw drastic changes to bariatric surgical practice, including postponement of procedures, altered patient care and impacting on the role of bariatric surgeons. The consequences of this both personally and professionally amongst bariatric surgeons has not as yet been explored. Aims The aim of this research was to understand bariatric surgeons' perspectives of working during the first year of the pandemic to explore the self‐reported personal and professional impact. Methods Using a retrospective, two phased, study design with global participants recruited from closed, bariatric surgical units. The first phase used a qualitative thematic analytic framework to identify salient areas of importance to surgeons. Themes informed the construction of an on‐line, confidential survey to test the potential generalizability of the interview findings with a larger representative population from the global bariatric surgical community. Findings Findings of the study revealed that the first year of the pandemic had a detrimental effect on bariatric surgeons both personally and professionally globally. Conclusion This study has identified the need to build resilience of bariatric surgeons so that the practice of self‐care and the encouragement of help‐seeking behaviors can potentially be normalized, which will in turn increase levels of mental health and wellbeing.